2016
DOI: 10.1016/j.nlm.2016.08.021
|View full text |Cite
|
Sign up to set email alerts
|

Gist extraction and sleep in 12-month-old infants

Abstract: Gist extraction is the process of excerpting shared features from a pool of new items. The present study examined sleep and the consolidation of gist in 12-month-old infants using a deferred imitation paradigm. Sixty infants were randomly assigned to a nap, a no-nap or a baseline control condition. In the nap and no-nap conditions, infants watched demonstrations of the same target actions on three different hand puppets that shared some features. During a 4-h delay, infants in the nap condition took a naturall… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 12 publications
(10 citation statements)
references
References 22 publications
0
9
0
Order By: Relevance
“…Indeed, experimental studies have provided evidence that sleep supports the retention and reorganization of memories even in infancy (Friedrich, Wilhelm, Born, & Friederici, ; Friedrich, Wilhelm, Mölle, Born, & Friederici, ; Gómez, Bootzin, & Nadel, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Liu, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Hupbach, Gomez, Bootzin, & Nadel, ; Konrad, Herbert, Schneider, Lorek, & Seehagen, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ; Simon et al., ). For the consolidation of early lexical–semantic memories, a benefit of sleep has been demonstrated by analyzing the looking behavior in 16‐month‐olds (Horváth et al., , ) and by measuring event‐related potentials (ERPs) in groups of 6‐ to 8‐ and 9‐ to 16‐month‐olds (Friedrich et al., , ).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, experimental studies have provided evidence that sleep supports the retention and reorganization of memories even in infancy (Friedrich, Wilhelm, Born, & Friederici, ; Friedrich, Wilhelm, Mölle, Born, & Friederici, ; Gómez, Bootzin, & Nadel, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Liu, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Hupbach, Gomez, Bootzin, & Nadel, ; Konrad, Herbert, Schneider, Lorek, & Seehagen, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ; Simon et al., ). For the consolidation of early lexical–semantic memories, a benefit of sleep has been demonstrated by analyzing the looking behavior in 16‐month‐olds (Horváth et al., , ) and by measuring event‐related potentials (ERPs) in groups of 6‐ to 8‐ and 9‐ to 16‐month‐olds (Friedrich et al., , ).…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, experimental studies have provided evidence that sleep supports the retention and reorganization of memories even in infancy (Friedrich, Wilhelm, Born, & Friederici, 2015;Friedrich, Wilhelm, Mölle, Born, & Friederici, 2017;Gómez, Bootzin, & Nadel, 2006;Horváth, Hannon, Ujma, Gombos, & Plunkett, 2018;Horváth, Liu, & Plunkett, 2016;Horváth, Myers, Foster, & Plunkett, 2015;Hupbach, Gomez, Bootzin, & Nadel, 2009;Konrad, Herbert, Schneider, Lorek, & Seehagen, 2015;Konrad, Herbert, Schneider, & Seehagen, 2016;Simon et al, 2017).…”
mentioning
confidence: 99%
“…Contrary to our second hypothesis, there was no difference in the likelihood of solely reproducing the relevant actions between infants in the nap and no-nap conditions. In light of recent evidence of sleep-dependent consolidation from imitation studies with samples of 6-and 12-month-olds (Konrad, Herbert, Schneider, & Seehagen, 2016;Seehagen et al, 2015) this is somewhat surprising, and could be due to several reasons. First, in these previous imitation studies there was some evidence for sleep being particularly helpful for memory consolidation when task difficulty was high, that is, overall imitation scores were modest after a delay.…”
Section: Discussionmentioning
confidence: 93%
“…It is well established that sleep after encoding facilitates the consolidation of both declarative and nondeclarative memories in human adults (Rasch & Born, ). A small but growing body of experimental research has revealed that postlearning sleep also facilitates the consolidation of recently encoded memories in infants across different paradigms (Friedrich, Wilhelm, Born, & Friederici, ; Horváth, Hannon, Ujma, Gombos, & Plunkett, ; Horváth, Myers, Foster, & Plunkett, ; Konrad, Herbert, Schneider, & Seehagen, ; Seehagen, Konrad, Herbert, & Schneider, ). For example, in a visual recognition memory paradigm, 3‐month‐olds were repeatedly shown a cartoon‐style face on a screen until their attention declined below a predefined criterion.…”
Section: Memory and Sleepmentioning
confidence: 99%
“…By embedding a new memory into existing related knowledge networks, sleep helps make memories retrievable through a wider range of cues related to the original experience (cf. Konrad et al., ). Although this distinction is plausible, it is difficult to tease apart the effects of postlearning sleep on memory retrieval versus memory consolidation.…”
Section: How Does Sleep Support Memory?mentioning
confidence: 99%